Crowdsourcing. A Citizen Participation Challenge - Borges, Junia; Zyngier, Camila (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper is a work in progress on Crowdsourcing. First, its concepts and importance are discussed and then its value for citizenship and urban planning. The motivation for participation and the display of geo-tagged information, as well as its possible applications in dynamic spatial temporal issues are presented, as well as its different approaches and applications. Furthermore, Crowdsourcing is discussed when the “ONVCêVIU”, a VGI case study, is presented, revealing its origin, objective, free platform comparison - to select the proper tool to implement, the project’s main challenges, results so far and further steps to be taken. To conclude a short review of the author’s vision about what is to come in the future research.